2014
DOI: 10.1038/tpj.2014.20
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of genetic polymorphisms associated with hepatitis C virus (HCV) antiviral response in a multiethnic and admixed population

Abstract: The prevalence of genetic polymorphisms identified as predictors of therapeutic-induced hepatitis C virus (HCV) clearance differs among ethnic groups. However, there is a paucity of information about their prevalence in South American populations, whose genetic background is highly admixed. Hence, single-nucleotide polymorphisms rs12979860, rs1127354 and rs7270101 were characterized in 1350 healthy individuals, and ethnicity was assessed in 259 randomly selected samples. The frequency of rs12979860CC, associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
2
8
0
1
Order By: Relevance
“…In this region, the high rate of infections with HCV genotype 1 and the high frequency in Native American populations of the TT genotype of IFNL4 SNP rs12979860 – markers associated with poor response to PEG-IFN/RBV therapy in both cases35,7578 – support the hypothesis that the implementation of IFN-free regimen should be beneficial in terms of cost–benefit. However, before or until global availability to DAAs is achieved, the identification of host predictive markers of antiviral therapy outcome could still be useful, as it will help prioritize DAA access.…”
Section: Implications In the Era Of Daasmentioning
confidence: 79%
See 3 more Smart Citations
“…In this region, the high rate of infections with HCV genotype 1 and the high frequency in Native American populations of the TT genotype of IFNL4 SNP rs12979860 – markers associated with poor response to PEG-IFN/RBV therapy in both cases35,7578 – support the hypothesis that the implementation of IFN-free regimen should be beneficial in terms of cost–benefit. However, before or until global availability to DAAs is achieved, the identification of host predictive markers of antiviral therapy outcome could still be useful, as it will help prioritize DAA access.…”
Section: Implications In the Era Of Daasmentioning
confidence: 79%
“…In this regard, recent studies have concluded that the distribution of these SNPs is closely related to the genetic ancestry in Latin America 35,7578. A study carried out among 2150 non-HCV-infected individuals from Argentina, Peru, Bolivia, and Paraguay, showed that the frequency of IFNL4 and ITPA SNPs exhibits a specific geographical pattern of distribution, even within the same country (Figures 2–4), and is closely related to the maternal and paternal ancestry of the population (Figures 5 and 6).…”
Section: Genetic Ancestry Influences Hcv Pharmacogenomics In Latin Ammentioning
confidence: 99%
See 2 more Smart Citations
“…In the United States, the rate of obtaining SVR in the black population is almost 50% less than of white patients, and the probability of obtaining SVR in white patients with HCV genotype 1 treated by PEG-IFN-α/R is approximately 42–53% [7]. In China, the SVR rate was a light higher, could reach 65.3% [8].…”
Section: Introductionmentioning
confidence: 99%